2010
DOI: 10.1101/gr.109231.110
|View full text |Cite
|
Sign up to set email alerts
|

The initial peopling of the Americas: A growing number of founding mitochondrial genomes from Beringia

Abstract: Pan-American mitochondrial DNA (mtDNA) haplogroup C1 has been recently subdivided into three branches, two of which (C1b and C1c) are characterized by ages and geographical distributions that are indicative of an early arrival from Beringia with Paleo-Indians. In contrast, the estimated ages of C1d-the third subset of C1-looked too young to fit the above scenario. To define the origin of this enigmatic C1 branch, we completely sequenced 63 C1d mitochondrial genomes from a wide range of geographically diverse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
192
1
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(221 citation statements)
references
References 40 publications
9
192
1
19
Order By: Relevance
“…group A, C, and D lineages in the pre-Hispanic Maya were consistent with the hypothesis that the direct ancestors of Native Americans were a hybrid of different Siberian groups that had migrated to eastern Beringia at different times and following different routes (Figure 4) (Kunz and Reanier 1994;Perego et al, 2010;Starikovskaya et al 2005). …”
Section: Network Analysis For Haplogroup Dsupporting
confidence: 86%
“…group A, C, and D lineages in the pre-Hispanic Maya were consistent with the hypothesis that the direct ancestors of Native Americans were a hybrid of different Siberian groups that had migrated to eastern Beringia at different times and following different routes (Figure 4) (Kunz and Reanier 1994;Perego et al, 2010;Starikovskaya et al 2005). …”
Section: Network Analysis For Haplogroup Dsupporting
confidence: 86%
“…20 In addition, complete mtDNA genome studies have shown that all pan-American mtDNA haplogroups reveal entry times of 15-18 Ka, which are suggestive of a concomitant post-Last Glacial Maximum arrival from Beringia with early Amerindians. [39][40][41][42] As for the question whether the Q1a3*-M346 was present in South Siberia in the post-Last Glacial Maximum, we can report that divergence time estimate for South Siberian versus Chinese/North Pakistan Q1a3*-M346 haplotypes is 15.29 ± 5.49 Ka, thus supporting the idea for the real presence of Q1a3*-M346 in South Siberia in those times.…”
Section: Discussionsupporting
confidence: 64%
“…El avance en las técnicas de análisis molecular que ha tenido lugar en los últimos años ha permitido superar la clásica distinción de cinco haplogrupos (hgs) nativos de América (A, B, C, D y X), identificándose actualmente por lo menos 13 subhaplogrupos que ya estaban diferenciados al momento de ingreso al continente americano (Tamm et al 2007;Malhi et al 2010;Perego et al 2010;Kumar et al 2011), algunos de los cuales presentan patrones de distribución que darían cuenta de distintas rutas de poblamiento, como el caso de D4h3a que se distribuye casi exclusivamente en el oeste del continente, desde Alaska hasta Tierra del Fuego y se asocia con un poblamiento por costa pacífica (Perego et al 2009). Asimismo, al interior de cada subhaplogrupo se está avanzando en la definición de clados con distribuciones geográficas acotadas, que se habrían diferenciado localmente (Gayà-Vidal et al 2011;Bodner et al 2012;de Saint Pierre et al 2012a,b;García et al 2012;Motti, 2012;Taboada-Echalar et al 2013).…”
Section: Antecedentes En Estudios De Adn Mitocondrialunclassified